Compression‐Tension‐Asymmetry and Stiffness Nonlinearity of Collagen‐Matrigel Composite Hydrogels - Böhringer, David; Hinrichsen, Jan; Gataulin, Radik; Wiedenmann, Sandra; Spörrer, Marina; Sherifova, Selda; Steinmann, Paul; Holzapfel, Gerhard A.; Fabry, Ben; Budday, Silvia (Advanced Healthcare Materials, 2025)
Collagen type I hydrogels, which self-assemble into 3D fiber networks, are commonly used for cell culture and tissue engineering applications. Collagen hydrogels replicate the nonlinear stress–strain relationship of collagenous tissue under extension. However, they buckle and soften under compression, whereas natural tissue exhibits significant stiffening due to the presence of cells and other matrix components. To more closely mimic the mechanical properties of natural tissue, varying concentrations of the basement membrane extract Matrigel are added to collagen. The stress–strain relationship of the resulting composite hydrogels is then analyzed under compression, tension, and shear. It is found that the addition of Matrigel increases the stiffness and reduces the compression-tension asymmetry. This can be explained by a reduced degree of freedom for collagen fiber buckling due to the constraints imposed by the surrounding fine-meshed Matrigel network. Consistent with this explanation, it is found that the collapse of composite hydrogels under uniaxial strain decreases with increasing concentration of Matrigel and other filler materials, such as alginate. Taken together, by adjusting the ratio of Matrigel to collagen, the mechanical compression-tension asymmetry and nonlinearity of composite hydrogels can be tuned to more closely mimic natural tissue and tailor cell behavio